The Effect of Added Carrageenan on Tensile Strength and Biodegradation of Edible Film using Breadfruit Starch - Maruf, Hidayatul; Dewata, Indang (Jurnal Kependudukan dan Pembangunan Lingkungan, 2022)
Breadfruit has a fairly high starch content of 84.28%, the utilization of breadfruit itself is still not optimal. In Indonesia, breadfruit can thrive in one of the breadfruit-producing cities, namely the city of Padang. One of the uses of breadfruit is in the manufacture of edible films. Edible film is a thin plastic that has a size smaller than 0.3 mm which serves to protect food products. The purpose of this study was to determine the effect of carrageenan on the tensile strength and biodegradation of edible films from breadfruit starch. This study used the addition of carrageenan with variations in concentrations of 0%, 0.5%, 1%, 1.5%, and 2%. Edible film was tested for tensile strength and obtained values ​​at 0% 2.046, 0.5% 4.252, 1% 7.678, 1.5% 4.139, 2% 3.829 where the optimum tensile strength value was at 1% with a tensile strength of 7.678 Mpa while the biodegradation had percent loss at least at a concentration of 2% with a percent loss yield of 11.5%. The higher the concentration used, the more difficult it is for the edible film to be degraded in the soil.